IDENTIFICATION OF SAFETY ALERT BY MONITORING ANALYTICAL PARAMETERS AND HIGH-RISK DRUGS - Vilaplana, Vicente Escudero-; AntÃºnez, MarÃa GÃ³mez-; GarcÃa, Esther DurÃ¡n-; MÃguez, Antonio MuiÃ±o-; SÃ¡ez, MarÃa Sanjurjo- (INDONESIAN JOURNAL OF PHARMACY, 2012)
Early detection of  adverse  drug  reactions  (ADR) increases patient  safety.  Our  objective  was  to  identify  ADR  by  monitoring laboratory  parameters  and  high-risk  drugs.  We  carried  out  a two-month  prospective  observational  study  in  a  Internal Medicine  Department,  with  daily  recording  of  drugs  prescribed and  the  following  parameters:  Na,  K,  Ca,  serum  creatinine, glomerular  filtration  rate  (GFR),  INR,  glucose,  haemoglobin, platelets,  ALT,  AST,  bilirubin,  GGT,  alkaline  phosphatase,  TSH, T4,  and  blood  digoxin.  High-risk  drugs  were  closely  monitored. 52  patients  included,  of  whom  46.2%  experienced  an  ADR.  We observed  an  association  with  drugs  in  25.5%,  as  follows: reduction  in  GFR,  26.9%  (associated  with  loop  diuretics [41.7%],  angiotensin-converting  enzyme  [ACE]  inhibitors [33.3%],  angiotensin  II  receptor  blockers  [ARB]  [16.6%],  andanti-diabetic  drugs  [8.3%]);  hypokalemia,  22.3%  (associated with  loop  diuretics  [50.0%],  potassium-free  fluid  [37.5%],  and salbutamol  [12.5%]);  hyperkalemia,  14.4%  (associated  with ACE  inhibitors  [60.0%]  and  ARB  [40.0%]);  INR  out  of  range, 10.8%  (associated  with  drug  interactions  [66.7%]); hyperglycemia,  8.1%  (associated  with  corticosteroids  [66.7%] and  anti-diabetic  drugs  [33.3%]);  and  other  conditions,  18.8%. We  conclued  that  patient  safety  could  be  improved  by implementing  warnings  in  electronic  prescriptions  in  cases  of  a decrease  in  GFR  or  modification  of  potassium  levels  in  patients who are prescribed loop diuretics, ACE inhibitors, or ARBs.Key words:   Adverse drug reaction,  clinical decision support,  high-risk drug, safety